2x+3y=8

Subtract 2x from both sides of the equation.

3y=8-2x

Divide each term by 3 and simplify.

Divide each term in 3y=8-2x by 3.

3y3=83+-2×3

Cancel the common factor of 3.

Cancel the common factor.

3y3=83+-2×3

Divide y by 1.

y=83+-2×3

y=83+-2×3

Move the negative in front of the fraction.

y=83-2×3

y=83-2×3

y=83-2×3

Choose any value for x that is in the domain to plug into the equation.

Remove parentheses.

y=83-2(0)3

Simplify 83-2(0)3.

Simplify each term.

Cancel the common factor of 0 and 3.

Factor 3 out of 2(0).

y=83-3(2⋅(0))3

Cancel the common factors.

Factor 3 out of 3.

y=83-3(2⋅(0))3(1)

Cancel the common factor.

y=83-3(2⋅(0))3⋅1

Rewrite the expression.

y=83-2⋅(0)1

Divide 2⋅(0) by 1.

y=83-(2⋅(0))

y=83-(2⋅(0))

y=83-(2⋅(0))

Multiply 2 by 0.

y=83-0

Multiply -1 by 0.

y=83+0

y=83+0

Add 83 and 0.

y=83

y=83

Use the x and y values to form the ordered pair.

(0,83)

(0,83)

Remove parentheses.

y=83-2(1)3

Simplify 83-2(1)3.

Multiply 2 by 1.

y=83-23

Combine the numerators over the common denominator.

y=8-23

Subtract 2 from 8.

y=63

Divide 6 by 3.

y=2

y=2

Use the x and y values to form the ordered pair.

(1,2)

(1,2)

Remove parentheses.

y=83-2(2)3

Simplify 83-2(2)3.

Multiply 2 by 2.

y=83-43

Combine the numerators over the common denominator.

y=8-43

Subtract 4 from 8.

y=43

y=43

Use the x and y values to form the ordered pair.

(2,43)

(2,43)

These are three possible solutions to the equation.

(0,83),(1,2),(2,43)

Find Three Ordered Pair Solutions 2x+3y=8